Cool Singapore: alternative nanomaterials (NMs) in IR reflectance - Lim, Joan Kai Li (2018)
Coloured geopolymer-based coatings were prepared using metakaolin and alkaline solution while varying the amount and type (with IR or NonIR reflectance properties) of pigments added. This coating, with the appropriate type and amount of pigments added, could be used as an alternative to conventional skim coat with cool paint. Cool coloured coating has high visible light reflectivity. In addition to that, adding IR pigments into cool coloured geopolymer-based coating could even enhance the radiation reflectivity, especially in the IR range. Using metakaolin, as the primary film forming material, regular maintenance and curing period could be reduced and at the same time, minimize carbon emission. The coatings’ mechanical, thermal emittance and solar reflectance performance were examined experimentally while varying the amount and type of pigment. After the evaluation of the results from surface reflectivity, compressive strength test and emissivity test, three specimens- pure metakaolin, 6% Shepherd/30C940 IR-black pigment and 6% Lanxess/ Bayferrox 360 NonIR-black pigment, were chosen for further experimental test- Thermal Behaviour Performance Test. 6% Shepherd/30C940 IR-black pigment specimen showed better mechanical, thermal and reflectance performance as compared to the other two specimens. This specimen exhibited good Infrared Radiation (IR) reflectance and emittance of absorbed energy while maintaining high compressive strength which performed better than pure metakaolin itself.